Association between Lifestyle Factors and Body Mass Index among Medical Technology/Medical Laboratory Science Students at the University of Mindanao, Philippines: A Cross-Sectional Study - Silguera, Junelle P. (Future Science / FSH-PH Publications, 2024)
This study investigates the factors influencing the Body Mass Index (BMI) status of Medical Technology/Medical Laboratory Science students at the University of Mindanao, Davao City, Philippines. Using a quantitative and descriptive design approach, 185 respondents were sampled using stratified and convenience sampling methods. The analysis included Frequency, Mean, Standard Deviation, and Ordinal Logistic Regression to assess diet, exercise, and pressure status as regressors of BMI. Findings reveal that respondents' age ranges from 17 to 24 years, with a mean BMI of 20.55, indicating normal weight status. First-year students predominantly participated, with more females than males. Most regularly consume breakfast, spend 6 to 10 minutes on meals, and engage in exercise sessions of less than 30 minutes, predominantly 1 to 3 times a week. Further, most respondents use mobile devices for 4 to 6 hours, and most prefer bedtimes from before 11:00 pm to 12:00 midnight. The final model highlights mealtime spent, exercise duration, and bedtime as significant regressors for BMI, emphasizing their association with lifestyle factors. These findings underscore the importance of academic institutions offering Medical Technology/Medical Laboratory Science courses to address obesity factors. Implementing awareness programs can empower students to make informed lifestyle choices.